"I can't cry on cue": Exploring distress experiences of persons with sickle cell - Janet E. Childerhose; Brent Emerson; Andrew Schamess; Jacqueline Caputo; Marcus Williams; Maryanna D. Klatt (Elsevier, 2024)
Persons with sickle cell disease exhibit high levels of distress, which has been documented with validated measures. However, there has been little qualitative investigation of the sources of distress in the lives of persons with sickle cell or the strategies they use to manage different sources of distress. Our study sought to: (1) identify sources of distress for persons with sickle cell, (2) explore management strategies for different sources of distress, (3) inform content development of the future mobile phone application, and (4) incorporate patient voices in the design and development phases of the future mobile phone application. In this manuscript, we present findings for the first objective. Using convenience sampling, we recruited participants with sickle cell (n = 11) from a home visit program at The Ohio State University Wexner Medical Center between February and July 2021. One team member conducted one-on-one semi-structured interviews with participants. We coded and analyzed all transcripts. Participants identified clinical encounters in the emergency department and intermediate care center to manage acute pain flares as the most profound source of distress. Our analysis identified four themes: (1) Pain has performative features, (2) Stigma and racism surround care, (3) Sickle cell is a neglected disease, and (4) Participants lack control over their pain management plan. Researchers may wish to consider how these settings can foster distress, and providers may wish to adopt participant recommendations to reduce distress associated with seeking pain treatment in acute care settings.